DARI SUMATERA KE KALIMANTAN: ADAPTASI SOSIAL BUDAYA MAHASISWA BARU ASAL SUMATERA UTARA DI PALANGKA RAYA - Batubara, Muhammad Zusanri Batubara (Universitas Hasanuddin, 2023)
Socio-cultural adaptation is mandatory for newcomers, including new students from North Sumatra. Adaptation is needed to get along, develop, and gain comfort in a new environment. The purpose of this study is to examine the process, obstacles, challenges and adaptation strategies of new students from North Sumatra in Palangka Raya. The research method used is a qualitative method with an ethnographic approach. The research data collection techniques include observation and interviews. Data analysis techniques include data collection, data reduction, and data presentation. The result of this study is that the adaptation process of new students from North Sumatra occurs through studying and understanding the socio-culture in Palangka Raya. Local students, regional organizations and churches from North Sumatra are used as socialization agents. The barriers and challenges are language, dialect, and culture shock. The strategy is to try to get to know better the socio-culture in Palangka Raya through socialization agents.